Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/plants11070855
|View full text |Cite
|
Sign up to set email alerts
|

The Phytoremediation Potential and Physiological Adaptive Response of Tamarix tetrandra Pall. Ex M. Bieb. during the Restoration of Chronosequence Fly Ash Deposits

Abstract: The challenging process of identifying and selecting plant species suited to the phytoremediation of fly ash (FA) dumps involves studying their functional properties and physiological response to a deficit of essential elements and toxicity from heavy metal(loid)-induced oxidative stress. We hypothesised that Tamarix tetrandra has high potential to be used for the phytoremediation of FA deposit sites thanks to its secretion strategy and antioxidative system. In this study, this hypothesis was examined by deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 94 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…Pontederiaceae, Asteraceae, and Fabaceae are the most representative plant families with a large number of species that bio-accumulate HMs [ 118 ]. Furthermore, recent studies have shown that the IPS can be used as biosensors for heavy metal-contaminated sites, such as Tamarix tetrandra Pall , Alliaria petiolata ( M. bieb ), Robinia pseudoacacia L., Miscanthus , Amorpha fruticosa L., and Populus alba L., and can eliminate different HMs with phytoremediation [ 119 , 120 ]. Wei et al [ 88 ] experimentally proved that C. odorata , B. pilosa , and P. clematidea enhance tolerance to Cd stress and have more ability to phytoextract Cd without morphological and physiological disturbance.…”
Section: Cleanup Environment From Hms By Ips Through Phytoremediationmentioning
confidence: 99%
“…Pontederiaceae, Asteraceae, and Fabaceae are the most representative plant families with a large number of species that bio-accumulate HMs [ 118 ]. Furthermore, recent studies have shown that the IPS can be used as biosensors for heavy metal-contaminated sites, such as Tamarix tetrandra Pall , Alliaria petiolata ( M. bieb ), Robinia pseudoacacia L., Miscanthus , Amorpha fruticosa L., and Populus alba L., and can eliminate different HMs with phytoremediation [ 119 , 120 ]. Wei et al [ 88 ] experimentally proved that C. odorata , B. pilosa , and P. clematidea enhance tolerance to Cd stress and have more ability to phytoextract Cd without morphological and physiological disturbance.…”
Section: Cleanup Environment From Hms By Ips Through Phytoremediationmentioning
confidence: 99%
“…Karst., Fagus sylvatica L., and Alnus glutinosa (L.) Gaertn. ( Gajić et al., 2020 ; Bęś et al., 2021 ; Kostic et al., 2022c ; Qadir et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of Cu, Ni, and Se were higher than the average for sandy to silt-loam substrates and concentrations of Mn and Zn were lower than the range of average values (<270 mg kg -1 and<45 mg kg -1 , respectively; Kabata-Pendias and Pendias, 2001 ). The surface association of As, B, Cr, and Zn on FA particles contributes to their greater solubility, making these elements extremely hazardous to plants at FA landfills if they are accumulated in high concentrations ( Gajić et al., 2020 ; Kostić et al., 2022b ; Kostic et al., 2022c ). However, it also contributes to their significantly lower content in FA at L11, although the content of B at L11 was still in the critical range for plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations